PS07 Trends in Blood Pressure in England: Good Treatment or Good Luck?. (17th September 2012) - DeWilde, SJ; Carey, IM; Shah, SM; Harris, T; Rudnicka, AR; Whincup, PH; Cook, DG
Abstract : Background: For 30 years, adult blood pressure (BP) has declined in many developed countries. This is likely to have contributed to declining cardiovascular disease mortality. However, the reasons for this, particularly the impact of increased antihypertensive treatment, have been little studied. Diagnostic criteria have changed, meaning that more patients are treated at lower levels of BP than previously; and treatment intensity is greater. Accounting for the effects of treatment on BP trends is complex and open to misinterpretation. Methods: Using the Health Survey for England we examined BP measures and treatment in white subjects aged 18+ years over two periods, 1994–2002 and 2003–2009. To examine trends independent of anti-hypertensive treatment, untreated BP was estimated from the recorded BP on treatment. To do this, a model was derived using published data on the effect of anti-hypertensives used singly and in combination at differing pre-treatment BP levels. BP untreated with statins was similarly estimated. Results: Among an average 9, 147 subjects per year, mean systolic BP (SBP) in men declined by 0.55 mmHg annually (95% CI 0.46 to 0.64) between 1995–2002; 0.34 mmHg annually (95% CI 0.21 to 0.46) between 2003–2009. Similar trends occurred in women. The decline was greater in older groups, but present in young, largely untreated groups, although the trend was greatly reduced in young men by 2009. Trends in estimated SBP adjusting for the influence of treatment, where present, exhibited only slightly lower declines; for men: 0.47 mmHg annually (95% CI 0.37 to 0.57) between 1995–2002; 0.27 mmHg annually (95% CI 0.13 to 0.41) between 2003–2009. Statin therapy had little additional effect. Diastolic blood pressure showed similar but weaker trends. Conclusion: For 15 years, BP declined in English adults. The overall decline in SBP of nearly 5 mmHg over the study period is likely to be of clinical significance in reducing CVD events. For an individual aged 40–49 a 5 mmHg reduction in SBP, as seen here, would be expected to reduce the risk of stroke by 23% and of IHD by 16%. It is therefore of concern that, in recent years, the decline has essentially ceased in the youngest age groups, particularly in younger men. The effect of treatment was modest; less than 25% of the male SBP decline is attributable to it. Other explanations for this fall, occurring whilst obesity has increased, need further exploration, but reduced salt intake is a likely candidate.